1997
DOI: 10.1038/sj.onc.1200857
|View full text |Cite
|
Sign up to set email alerts
|

The Eek receptor, a member of the Eph family of tyrosine protein kinases, can be activated by three different Eph family ligands

Abstract: The Eph family of receptors, the largest subgroup within the tyrosine protein kinase receptor family, are comprised of at least thirteen members, many of which are predominantly expressed in the developing and adult nervous system. In this study, we have isolated a fulllength cDNA, encoding the mouse homologue of a previous partially characterized Eek protein, a member of Eph receptor tyrosine kinase family. In a comparison of the amino acid sequences of various Eph family members, Eek is most similar to Ehk-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…1A, bottom), it was evident that both EphA8-TrkB and EphA8 proteins were highly tyrosine phosphorylated due to the endogenous expression of EphA subgroup ligands as described previously (Fig. 1A, bottom, lanes 3 to 5) (30). In contrast, the EphA8 mutant containing Met in place of Lys-666, the putative ATP binding residue, was not tyrosine phos-phorylated (Fig.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…1A, bottom), it was evident that both EphA8-TrkB and EphA8 proteins were highly tyrosine phosphorylated due to the endogenous expression of EphA subgroup ligands as described previously (Fig. 1A, bottom, lanes 3 to 5) (30). In contrast, the EphA8 mutant containing Met in place of Lys-666, the putative ATP binding residue, was not tyrosine phos-phorylated (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…To further exclude the possibility that EphA8 promotes integrin activity by activating ligand signaling pathways, NIH 3T3 cells were treated with PI-PLC, which eliminates GPI-linked ephrin A subgroup ligands from the cell surface as previously reported (30). We then compared the ability of the ephrin A-stripped cells to adhere to surfaces coated with fibronectin with or without preclustered ephrin A5-Fc soluble ligand stimulation (see Fig.…”
Section: Vol 21 2001 Regulation Of Integrin Activity By Epha8 4583mentioning
confidence: 99%
See 1 more Smart Citation
“…Prevous studies demonstrated that ephrinA5-Fc binds to the EphA8 receptor with high nM affinity (Park and Sanchez, 1997), and that treatment with its aggregated forms stimulates cell migration on the fibronectin substrate (Gu and Park, 2003). These studies clearly indicate that ephrin-A5 is an authentic ligand for EphA8.…”
Section: Discussionmentioning
confidence: 95%
“…EphA8 receptors can bind at least three different type A ephrins (Park and Sµnchez 1997), but the one (or those) that play(s) a role in the formation of the projection from the superior colliculus to the contralateral inferior colliculus is (are) unclear. Engrailed homeobox genes regulate the expression of molecular cues (possibly ephrins) that direct growing retinal axons in the tectum to their correct topographic location.…”
Section: Genetic Studies: Mice Lacking Epha8 Receptorsmentioning
confidence: 99%